SISTEM INFORMASI APOTEK DARUL HAYYI MENGGUNAKAN MACRO MICROSOFT EXCEL - Aditya Aulia Rahim Putri Lannar, Rosi; Rudzali, Achmad (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2024)
This study aims to find out how to design and create pharmacy applications using Microsoft Excel Macros at Darul Hayyi Pharmacy. The object of this research is Darul Hayyi Samarinda Pharmacy. Data collection techniques are observation, interviews, and literature studies. The analysis tool used is the Microsoft Excel Macros program. The results of this study show that by applying Microsoft Excel Macros to the pharmacy information system, it can provide several advantages such as facilitating work or activities related to the Darul Hayyi Pharmacy Information System, such as inputting master data, inputting over-the-counter drug sales activities and drug sales with a doctor's prescription, and purchasing drug supplies. The speed and accuracy of accessing data makes it easy to create the reports needed. And by using Microsoft Excel Macros can minimize errors that usually occur if done manually